Case Report: Nephrotic Syndrome in a 27-Year-Old Male Patient - Novianto, Ichsan; Hidayat, Nur (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Nephrotic syndrome (SN) is a glomerular disorder characterized by severe proteinuria, hypoalbuminemia, hyperlipidemia, and peripheral oedema. The annual incidence of nephrotic syndrome in adults is three per 100,000 people. Case: A 27-year-old man came to the Internal Medicine Polyclinic with complaints of swelling throughout the body. Swelling was felt since 2 weeks ago, initially swelling in the face and eyelid area then increased in weight to the whole body. The patient often takes stall medicine Paracetamol when headache is felt. The eyes were found to have palpebral swelling (+/+). Physical examination of the abdomen revealed distension, undulation test was positive and shifting dullness was positive indicating ascites. Examination of the inferior and superior extremities revealed pitting oedema on all four extremities (+/+/+/+). Examination of genitalia on inspection found the scrotum looks erythema, swollen, scrotum painful when moved, negative phren sign, negative cremaster reflex.